The Precondition Model as a method for developing understanding of female contact and non-contact sex offending: a single case study - Collins, Sophia; Duff, Simon (Emerald, 2016)
This research evaluates the use of an established model, typically used for understanding male sex offenders, to understand the behaviour of a female sex offender. The Finkelhor (1984) Precondition Model of offending is used to provide a rare opportunity to explore the process of offending for a female contact and non-contact offender, whose offences were against children. It reviews the efficacy of utilising this model in the rehabilitation and collaborative risk management of a female sex offender. The results suggest that this approach can be applied to internet and contact sex offences to develop understanding of the progression of offending, including issues such as sexual arousal and the impact of a male co-perpetrator. In this case, the results indicate a post-intervention improvement in areas such as affect control, ability to maintain positive relationships, self-support, and reduced dissociation and dysfunctional sexual behaviour. This project provides support for the development of a treatment approach that explores the individual nuances of female sex offending.